The Use of Digital Mind Mapping to Improve EFL Student’s Ability in Writing Descriptive Paragraph - Sudibyo, Hari Laksono (RETAIN : Journal of Research in English Language Teaching, 2022)
Abstract This study aims to know if there is any improvement in writing descriptive paragraphs taught before and after using digital mind mapping. A quantitative approach was used in this study, with a pre-experimental research design. The subject of this study is VIII-A grades, and the participants are 20 students. Testing is the instrument used in this study; there are two types of tests: pretest and posttest. This study showed that the pretest score was 49.0625, and the posttest score was 79.0625. Using SPSS Statistics 18, the mean score of the posttest was higher than the mean score of the pretest. The significance of the two-tail shown was 0,000, which means that the result of the significant level was the considerable standard level (0, 00 0, 05). According to data analysis, Tcount is bigger than To The alternative hypothesis (Ha) accepted, and the null hypothesis (Ho) rejected. It indicates that the use of digital mind mapping effectively improved students’ descriptive paragraph writing. Keywords: Writing, Digital Mind Mapping, Descriptive Paragraph